"I Wouldn't Mind Trying It. I'm in Pain the Whole Time": Barriers to the Use of Complementary Medicines by Older Australians in Residential Aged-Care Facilities. (September 2017) - Rayner, Jo-Anne; Bauer, Michael
Older people living in the community use complementary medicine (CM) to manage the symptoms of chronic illness; however, little is known about CM use by older people living in care settings. Using focus groups and individual interviews, this study explored the use of CM from the perspective of 71 residents, families, and health professionals from six residential aged-care facilities in Victoria, Australia. Residents used CM to manage pain and improve mobility, often covertly, and only with the financial assistance of their families. Facility policies and funding restrictions constrained CM use at the individual and facility level. An absence of evidence to support safety and efficacy coupled with the risk of interactions made doctors wary of CM use in older people. These findings have relevance for the large number of CM using "baby-boomers" as they move into residential aged-care.